Synthesis, antiphospholipase A2, antiprotease, antibacterial evaluation and molecular docking analysis of certain novel hydrazones - El-Sayed, Nahed Nasser Eid; Alafeefy, Ahmed Mahmoud; Bakht, Mohammed Afroz; Vijay H., Masand; Aldalbahi, Ali; N., Chen; C., Fan; Bacha, Abir Ben Ben (MDPI AG, 2016)
Some novel hydrazone derivatives 6a-o were synthesized from the key intermediate 4-Chloro-N-(2-hydrazinocarbonyl-phenyl)-benzamide 5 and characterized using IR, 1H-NMR, 13C-NMR, mass spectroscopy and elemental analysis. The inhibitory potential against two secretory phospholipase A2 (sPLA2), three protease enzymes and eleven bacterial strains were evaluated. The results revealed that all compounds showed preferential inhibition towards hGIIA isoform of sPLA2 rather than DrG-IB with compounds 6l and 6e being the most active. The tested compounds exhibited excellent antiprotease activity against proteinase K and protease from Bacillus sp. with compound 6l being the most active against both enzymes. Furthermore, the maximum zones of inhibition against bacterial growth were exhibited by compounds; 6a, 6m, and 6o against P. aeruginosa; 6a, 6b, 6d, 6f, 6l, 6m, 6n, and 6o against Serratia; 6k against S. mutans; and compounds 6a, 6d, 6e, 6m, and 6n against E. feacalis. The docking simulations of hydrazones 6a-o with GIIA sPLA2, proteinase K and hydrazones 6a-e with glutamine-fructose-6-phosphate transaminase were performed to obtain information regarding the mechanism of action.